Rahnella aquatilis Sepsis in a Premature Newborn - Canan Kuzdan; Ahmet Soysal; Hülya Özdemir; Şenay Coşkun; İpek Akman; Hülya Bilgen; Eren Özek; Mustafa Bakır (Case Reports in Pediatrics)
Rahnella aquatilis is an infrequently isolated Gram-negative rod within the Enterobacteriaceae family. The organism’s natural habitat is water. The organism is rarely isolated from clinical specimens and it seldom causes infection in immunocompetent individuals. Here we present a one-month-old boy who was born prematurely at 27th week of gestation by cesarean section with a birth weight of 730 g. He developed sepsis caused by Rahnella aquatilis during the treatment for ventilator associated pneumonia due to Stenotrophomonas maltophilia with ciprofloxacin. He was successfully treated with a combination of amikacin plus meropenem. Although R. aquatilis is one of the saprophyticus organisms, it may cause life-threatening infection in newborn.